3x+5-5*x+1=6x+7

Simple and best practice solution for 3x+5-5*x+1=6x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5-5*x+1=6x+7 equation:


Simplifying
3x + 5 + -5x + 1 = 6x + 7

Reorder the terms:
5 + 1 + 3x + -5x = 6x + 7

Combine like terms: 5 + 1 = 6
6 + 3x + -5x = 6x + 7

Combine like terms: 3x + -5x = -2x
6 + -2x = 6x + 7

Reorder the terms:
6 + -2x = 7 + 6x

Solving
6 + -2x = 7 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
6 + -2x + -6x = 7 + 6x + -6x

Combine like terms: -2x + -6x = -8x
6 + -8x = 7 + 6x + -6x

Combine like terms: 6x + -6x = 0
6 + -8x = 7 + 0
6 + -8x = 7

Add '-6' to each side of the equation.
6 + -6 + -8x = 7 + -6

Combine like terms: 6 + -6 = 0
0 + -8x = 7 + -6
-8x = 7 + -6

Combine like terms: 7 + -6 = 1
-8x = 1

Divide each side by '-8'.
x = -0.125

Simplifying
x = -0.125

See similar equations:

| C=D+Drt | | 6+w/5=21 | | -4x=x+15 | | 1.5=0.75a | | 0=-3x^2+-54x+-240 | | 4x+2x+5-x=10x+10 | | y=-3x^2+-54x+-240 | | 6(3x+2)=48 | | 15=2w+5 | | -7x=x+24 | | 4X+3=X+8+187 | | 2.5-.5x+3=5+2.5-5x | | -12=6x^2-22x | | -3(4y-2)-y=-4(y-5) | | 56-v=v^2 | | ln(x)=1.8 | | lnx=1.8 | | 9(x+15)=25 | | x^2=110-n | | 4x=-x-10 | | N^2=110-n | | y=-1(-1-11) | | x^2-16x-27=10 | | p(p-4)= | | 3x+15=3(2x+2) | | x+9+2x=-24 | | 90-x=x^2 | | x+7=5x | | a=8-1 | | 7x-10y-10x+5y=0 | | -3+2y=10 | | -4*5-9=d |

Equations solver categories